2018
DOI: 10.1016/j.pneurobio.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of placebo analgesia: A dual-process model informed by insights from cross-species comparisons

Abstract: Placebo treatments are pharmacologically inert, but are known to alleviate symptoms across a variety of clinical conditions. Associative learning and cognitive expectations both play important roles in placebo responses, however we are just beginning to understand how interactions between these processes lead to powerful effects. Here, we review the psychological principles underlying placebo effects and our current understanding of their brain bases, focusing on studies demonstrating both the importance of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 306 publications
(502 reference statements)
2
35
0
1
Order By: Relevance
“…There could be several reasons for the lack of placebo analgesia in the present study, as noted. Placebo analgesia is mainly a top-down process initiated in frontal regions associated with expectations of treatment effects, that in turn activate mid-brain areas involved in modulation of pain via descending pathways ( Schafer et al, 2018 ). In effect, reduced activity in pain-responsive areas in the brain has often been observed (e.g., Wager et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…There could be several reasons for the lack of placebo analgesia in the present study, as noted. Placebo analgesia is mainly a top-down process initiated in frontal regions associated with expectations of treatment effects, that in turn activate mid-brain areas involved in modulation of pain via descending pathways ( Schafer et al, 2018 ). In effect, reduced activity in pain-responsive areas in the brain has often been observed (e.g., Wager et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example the dorsolateral prefrontal cortex (dlPFC) -a brain region involved in high-level 20 cognitive functions -responds to painful stimulation, shows alterations in chronic pain 21 conditions, and contributes to placebo analgesia (Krummenacher et al, 2010;Bushnell et al, 22 2013;Seminowicz and Moayedi, 2017;Schafer et al, 2018). Other brain regions, including the 23 ventromedial prefrontal cortex (vmPFC) Roy et al, 2012;Geuter et al, 2017b) 24 and the nucleus accumbens (NAc) (Baliki et al, 2012;Chang et al, 2014;Lee et al, 2015;Woo 25 et al, 2015;Ren et al, 2016), key structures for reinforcement learning, also contribute to pain 26 modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct pharmacological mechanisms underlying expectation and conditioning have been revealed by a carefully designed human study, which has shown that expectation triggers endogenous opioids, while conditioning activates specific subsystems not necessarily dependent on the opioid system [ 44 ]. Expectation-dependent placebo analgesia mediated by the opioid system has been reliably reported in the literature [ 45 ]. Morphine (an opiate analgesic)-induced placebo analgesia is dependent on expectation and can be blocked by opioid antagonists.…”
Section: Discussionmentioning
confidence: 99%